FEATURE AND FUNCTIONS WERDS IN THE LITERARY LANGUAGE - Rahimberdiyev, Maqsadbek; Tojibaev, Isoqjon (Educational Research in Universal Sciences, 2023)
This article provides information on Shakespeare’s morphology. His poems are morphologically analyzed and sources related to poetry are presented. Grammatical problems are studied.In addition, in this article Shakespeare’s works are analyzed.